Profesionalisme Kepemimpinan Kepala Sekolah dan Kinerja Guru dalam Peningkatan Prestasi Belajar Siswa - Achmad Naim (Program Pascasarjana Universitas Ibrahimy, 2017)
The learning process is considered successful when the ability to absorb the teaching material has reached high achievement, both individual and group and the behavior in the specific instructional objectives has been achieved by students. Teachers as learning designers have a role in designing learning to produce optimally students achievement. The headmaster as a leader has a role to create a conducive and controlled school so that produces the best graduates. This research tries to analyze about professionalism of headmaster and teacher in improving student achievement. In this study found the conclusion that the success of students can be achieved due to students’ internal factors and external factors such as environment, school leadership, teacher methods in teaching and learning climate.